Preliminary Study of Liquid Hydrocarbon Biodegradation By Indigineous Bacteria Isolated from Wonocolo Village, Bojonegoro District, East Java Province - Wahyu Wilopo; Bramono Dwi Kusumo; Endah Retnaningrum (Geological Engineering Department Universitas Gadjah Mada, 2018)
Aquatic environmental pollution due to petroleum waste can cause disruption to the environment and damaging of flora and fauna. It has been reported that petroleum contaminatin occurs in the Bengawan Solo river, East Java Province. Liquid hydrocarbon waste pollution can be remediate through various processes, one of them is biodegradation. Biodegradation a part of bioremediation, is the process by which organic substances are decomposed by microorganisms into simpler substances such as carbon dioxide, water and ammonia. Bioremediation has minor side effects compare to other methods because it’s more effective, efficient, economical and eco-friendly through biological process. This study aims to identify bacteria for liquid hydrocarbon degradation from the rivers in Wonocolo Village, Bojonegoro District and to determine maximum percentage of inoculum to produce the highest efficiency of liquid hydrocarbons degradation. Based on phenotypic characters, the selected bacteria was identified as a genus of Moraxella. Its bacterium with a concentration of 2 % can reduce hydrocarbons to a maximum of 0.67 % per hour at the exponential phase growth.